SETTLEMENT OF DISPUTES THROUGH MEDIATION OF BANKING - Amelia Kandisa2, Luh Putu Vera Astri Pujyanti1 (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The purpose and goal of this research  is to analyze the  banking dispute resolution procedures  between the Bank  and the Customer by the Institute  for Mediation and Court Banking.  The results of the study suggest  if there is a dispute between the customer and the bank, the banking mediation is an option that is very effective, because in addition to greatly shorten the time was  also the result of mediation can be executed by both parties to the dispute. Obtained agreement from the mediation process set out in a deed agreement, which shall be final and binding on the customer and the  bank. Is defined as final, the dispute can not be asked to do the re mediation process mediation executive function , and is intended to bind the agreement applies as Legislation.  However, if the tow sides do not agree and can not find a good meeting point between the customer and the bank, the parties may file a degree of mediation court.Keywords :  Dispute resolution, Mediation,  Banking